An old Drug with a New Paradigm? A Review Article on Thalidomide Use in Recurrent Small-Intestinal Angiodysplasia Bleed - Calvin Ghimire; Jerry Kenmoe; Nikky Maharjan; Sajan Acharya; Sanjana Poudel; Alex Rabadi; Matthew Jankowski; Manoj Ghimire; Rohit Rauniyar; Bibek Karki; Ujwala Koduru; Sushila Adhikari Phar; et al. (Medical – Clinical – Research, 2026)
Angiodysplasia, a prevalent vascular anomaly, is a significant cause of obscure gastrointestinal bleeding (OGIB) in individuals over 60. Thalidomide, known for its antiangiogenic properties, has shown promise in managing gastrointestinal angiodysplasia (GIAD) by inhibiting proangiogenic factors. This review evaluates the efficacy and safety of thalidomide in reducing bleeding episodes and improving clinical outcomes in patients with recurrent small intestinal angiodysplasia bleeding. A comprehensive literature search was conducted in PubMed, Cochrane, and Embase databases, including both case reports and randomized controlled trials (RCTs) related to thalidomide and recurrent small intestinal angiodysplasia bleeding. Data extraction and quality assessment were performed independently by two reviewers. The results were synthesized narratively and grouped based on similar characteristics. Thalidomide demonstrated significant efficacy in reducing bleeding episodes, with response rates of 68.6% in the 100 mg group and 51.0% in the 50 mg group, compared to 16.0% in the placebo group. However, adverse events such as constipation, somnolence, and limb numbness were more common in the thalidomide groups. Albeit there exist clinical cases of the effectiveness of thalidomide, with patients achieving stable hemoglobin levels and cessation of blood transfusions after treatment. Thalidomide shows potential as a therapeutic option for managing recurrent small intestinal angiodysplasia bleeding. However, its use is limited by significant adverse effects. Further research is necessary to refine dosing strategies and assess long-term safety.